Insulin Sensitization by PPARγ and GLUT-4 Overexpression/Translocation Mediates the Antidiabetic Effect of Plantago australis - Samuel Estrada-Soto; Kathia Ornelas-Mendoza; Gabriel Navarrete-Vázquez; Fabiola Chávez-Silva; Julio Cesar Almanza-Pérez; Rafael Villalobos-Molina; Erandi Ortiz-Barragán; Hilda Loza-Rodríguez; Julio César Rivera-Leyva; Angélica Flores-Flores; Irene Perea-Arango; Javier-German Rod; et al. (MDPI AG, 2023)
Plantago australis Lam. Subsp. hirtella (Kunth) Rahn is a medicinal plant used as a diuretic, anti-inflammatory, antibacterial, throat cancer treatment and for the control of diabetes. P. australis was collected in the state of Morelos, México. The hydroalcoholic extract (HAEPa) of P. australis was obtained by maceration and concentrated in vacuo. Once dry, it was evaluated through an oral glucose tolerance test (OGTT) in normoglycemic mice and in a non-insulin-dependent diabetic mice model. The expression of PPARγ and GLUT-4 mRNA was determined by rt-PCR, and GLUT-4 translocation was confirmed by confocal microscopy. The toxicological studies were conducted in accordance with the guidelines suggested by the OECD, sections 423 and 407, with some modifications. HAEPa significantly decreased glycemia in OGTT curves, as well as in the experimental diabetes model compared to the vehicle group. In vitro tests showed that HAEPa induced an α-glucosidase inhibition and increased PPARγ and GLUT-4 expression in cell culture. The LD50 of HAEPa was greater than 2000 mg/kg, and sub-chronic toxicity studies revealed that 100 mg/kg/day for 28 days did not generate toxicity. Finally, LC-MS analysis led to the identification of verbascoside, caffeic acid and geniposidic acid, and phytochemical approaches allowed for the isolation of ursolic acid, which showed significant PPARγ overexpression and augmented GLUT-4 translocation. In conclusion, HAEPa induced significant antidiabetic action by insulin sensitization through PPARγ/GLUT-4 overexpression.